Patentability conditions for the invention protection - Čabarkapa, Obrad T.; Petrović, Dalibor P.; Dunjić, Marina S. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Summary: Invention occurs as a result of creative work protected by a patent or petty patent, provided that the patent was filed. Inventions are the kinds of innovations that have a technical character because offer solutions for technical problem and it can relate to any area of technique. Basically, each invention has specific tehnical characteristics, which are case protection (correctly defined the through patents claims). Patent protection is the right which admits the holder to achive the goal of economic exploitation of the invention. In order to get an invention patent protection, invention should be patentable, and that meets the following requirements: the existence of invention, novelty, inventive step and industrial applicability of the invention. In general, the study of these conditions, we should start from the national legislation in the area of patent protection, which specifying what can not be considered about the invention and what can not be protected by a patent or petty patent Examination of patentability is made in a particular stage of the procedure examination by experts in the technical field to which the invention relates. If all required conditions, it is said that the invention is patentable and it can be done patent protection.  Keywords: The invention, patentability, patent, petty patent, novelty of the invention, inventive step, industrial applicability of the invention.
Keywords: protective; Patents; invention